Adaptive Tourism Management Strategies for Nature-Based Destinations in Ecological Disaster Mitigation: Evidence from Sibolga, Indonesia - Aditiya Pratama Daryana; Vina Gabriella Saragih; Prima Yudisthira (Jurnal Inovasi Bisnis dan Kewirausahaan, 2026)
This study aims to analyze adaptive tourism management strategies in ecological disaster mitigation for nature-based tourism destinations in Sibolga, Indonesia. A case study approach was applied using qualitative methods supported by descriptive quantitative data collected through interviews, focus group discussions, field observations, and policy document analysis. The findings indicate that policy flexibility, stakeholder collaboration, and institutional learning have been partially implemented as adaptive practices, although the integration of ecological risk into destination planning remains weak. Adaptive tourism management plays a critical role in risk reduction and destination preparedness. The study concludes that embedding adaptive management within everyday destination governance can significantly enhance destination resilience to ecological pressures and support the long-term sustainability of coastal tourism.